2014
DOI: 10.1002/apj.1855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an ionic liquid as an additive on the thermal denaturation/degradation of lysozyme crystals

Abstract: Ionic liquids (ILs) have biomaterial applications and are used for protein crystallization. The present study explores the thermal denaturation and degradation kinetics of the lysozyme crystals induced by IL [C4mim]Cl using differential scanning calorimetry (DSC). Lysozyme crystals were scanned from 10 to 250 °C at different heating rates varying from 5 to 20 °C min−1. Under the same heating rate, the addition of the IL makes lysozyme crystals confer more resistance to thermal denaturation and change values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Soft anions such as formate or glycolate are superior to ILs with hard anions, like nitrate, in promoting crystallization. Wang et al reported enhanced thermal resistance of lysozyme crystals prepared in 1% [C 4 mim]­Cl, which is due to the change in lysozyme-lysozyme molecular interactions. This IL promoted the nucleation of crystals with small size, lower surface free energy, and improved morphology.…”
Section: Ionic Liquid-protein Systemsmentioning
confidence: 99%
“…Soft anions such as formate or glycolate are superior to ILs with hard anions, like nitrate, in promoting crystallization. Wang et al reported enhanced thermal resistance of lysozyme crystals prepared in 1% [C 4 mim]­Cl, which is due to the change in lysozyme-lysozyme molecular interactions. This IL promoted the nucleation of crystals with small size, lower surface free energy, and improved morphology.…”
Section: Ionic Liquid-protein Systemsmentioning
confidence: 99%
“…ILs can enhance the stability of the protein conformation and activity, 58 and even affect the renaturation of some recombinant proteins. 59 Wang et al explored the thermal denaturation and degradation kinetics of lysozyme crystals induced by ILs, 60 and lysozyme crystals were found to be more resistant to thermal denaturation in the presence of ILs. Shaposhnikova et al investigated the structural basis of the interactions between the ILs and proteins.…”
Section: Additivesmentioning
confidence: 99%